1993
DOI: 10.1007/bf00797829
|View full text |Cite
|
Sign up to set email alerts
|

Suicide in Hong Kong 1971?1990: age trend, sex ratio, and method of suicide

Abstract: This study gives an overview of the suicide rates in Hong Kong in the last 2 decades (1971-1990). It was found that the average suicide rate for the whole population was 11.3 per 100,000 population and it has been quite steady in recent years. The male and female adolescent (age-group 10-24 years) suicide rates were approximately the same, while the ratio of the overall male to female rate was 1.3:1. This indicated a relatively high female rate as compared with other countries. An examination of the suicide ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 23 publications
2
25
0
Order By: Relevance
“…This finding contradicts the all India figure (1.4:1), 1 so also in other regional countries like Thailand 12 and Hong Kong. 13 Studies in other parts of the world also showed male predominance in suicides like in Cork City, 5 in South Carolina, USA 4 and in Geneva. 6 A study in England and Wales suggests that there is an increase in the rate of suicide in both sexes but greater in males.…”
Section: Discussionmentioning
confidence: 95%
“…This finding contradicts the all India figure (1.4:1), 1 so also in other regional countries like Thailand 12 and Hong Kong. 13 Studies in other parts of the world also showed male predominance in suicides like in Cork City, 5 in South Carolina, USA 4 and in Geneva. 6 A study in England and Wales suggests that there is an increase in the rate of suicide in both sexes but greater in males.…”
Section: Discussionmentioning
confidence: 95%
“…Some studies have further examined the suicide trend in Hong Kong (26) and compared the related phenomena in Hong Kong with those in Taiwan (27). Yip (28) compared statistics on suicide in Hong Kong, Taiwan and Beijing and concluded that while there was a significant increase in the suicide rate among adolescents aged [15][16][17][18][19][20][21][22][23][24] in Hong Kong in the 1980s, suicide rates of youth in both Taiwan and Beijing declined in the same period.…”
Section: Adolescent Suicide γν Hong Kongmentioning
confidence: 99%
“…Yap (1958) published the first study of suicidal behaviour in Hong Kong. ~'hc papers of Yap (1958), Lo and Leung (1985), Hau (1993), Ho et al (1995), Ho (1996) showed that Hong Kong had a rather stable crude suicide rate, a low gender ratio (male:female), high elderly and low teenage suicide rates. Yip (1996a) used a component analysis method to examine the change of the crude suicide rate for the period [1981][1982][1983][1984][1985][1986][1987][1988][1989][1990][1991][1992][1993][1994].…”
Section: Introductionmentioning
confidence: 98%